Hubungan Kepercayaan Diri dan Pemilihan Karir siswa MA Miftahul Jannah Palangka Raya - Rusdi Rusdi (Syams, 2022)
This study aims to determine the relationship between self-confidence and career choice of MA Miftahul Jannah students in Palangka Raya. The population in this study were all students of class X MA Miftahul Jannah Palangka Raya. The sampling technique used simple random sampling with a total sample of 60 students. Data were collected through self-confidence questionnaires and career selection interviews. Data analysis used the Pearson correlation test. The results of the study show that there is a positive and significant relationship between self-confidence and the career choice of MA Miftahul Jannah students in Palangka Raya. The correlation coefficient value is 0.471 and a significant value is 0.000 (p 0.05).Keywords: self-confidence, career choice, students.